التعليم الثانوي والمهني في مدينة كربلاء المقدسة 1968-1979 - الحلو، نبيل جواد عطية; الجزائري، محمد جواد جاسم محمد (جامعة الكوفة - كلية الآداب, 2023)
تناول الباحث دراسة التعليم في مدينة كربلاء المقدسة، كونها من المدن التاريخية الإسلامية المهمة، التي كانت مدارسها الدينية مزدهرة في الدراسة لاسيما الحوزوية منها، فقد ضمت حلقات الدرس فيها كثير من العلماء والفقهاء، فساهم التعليم في تنمية قدرات الطلبة بالعلوم والمعارف والقيم النبيلة والمهارات والتوجهات التي تمكنهم من مواجهة متطلبات الحياة اليومية، فضلا عن مستواهم الخدمي والصحي، مما تزاد من فرص مشاركتهم في الحياة السياسية، ومكنهم من المساهمة بشكل أفضل في التنمية الاقتصادية لبلادهم، وتقليص حالة الفقر والجهل لديهم، وقد اختار الباحث المدة الزمنية 1968- 1979 لدراسته كونها مرحلة زمنية اختلفت في سماتها وخصائصها عما قبلها في كافة المجالات ومنها مجال التعليم وتطوره. The researcher dealt with the study of education in the holy city of Karbala, as it is one of the important historical Islamic cities, whose religious schools were flourishing in study, especially the seminary ones. It enables them to meet the requirements of daily life, in addition to raising their level of service and health, which increases the chances of their participation in political life, and enables them to contribute better to the economic development of their country, and reduce their poverty and ignorance. The researcher chose the time period 1968-1979 for his study as being A period of time that differed in its features and characteristics from those before it in all fields, including the field of education and its development.
Keywords: التعليم الثانوي -- المدن التاريخية -- التعليم المهني -- التراث الإسلامي -- العراق